A systematic review of randomized controlled trials investigating the efficacy and safety of testosterone therapy for female sexual dysfunction in postmenopausal women. (14th January 2019) - Jayasena, Channa N.; Alkaabi, Fatima M.; Liebers, Curtis S.; Handley, Thomas; Franks, Stephen; Dhillo, Waljit S.
Summary: The clinical sequelae of oestrogen deficiency during menopause are undoubted. However, the pathophysiological role of testosterone during the menopause is less clear. Several randomized, placebo‐controlled clinical trials suggest that testosterone therapy improves sexual function in postmenopausal women. Some studies suggest that testosterone therapy has additional effects, which include increased bone mineral density and decreased serum high‐density lipoprotein (HDL) cholesterol. Furthermore, the long‐term safety profile of testosterone therapy in postmenopausal women is not clear. This article will provide a concise and critical summary of the literature, to guide clinicians treating postmenopausal women.